Ibn al-Mubārak’s Kitāb al-Jihād and Early Renunciant Literature - Melchert, C (Edinburgh University Press, 2015)
‛Abd Allāh ibn al-Mubārak (d. Hit, 181/797) was a famous traditionist, whose three main works are here surveyed, with stress on overlap between the Jihad and the Zuhd. The renunciant tradition appears to have influenced the legal tradition concerning jihad.